2006
DOI: 10.1021/bi060899i
|View full text |Cite
|
Sign up to set email alerts
|

Tropomodulin Binds Two Tropomyosins:  A Novel Model for Actin Filament Capping

Abstract: Tropomodulin, a tropomyosin-binding protein, caps the slow-growing (pointed) end of the actin filament regulating its dynamics. Tropomodulin, therefore, is important for determining cell morphology, cell movement, and muscle contraction. For the first time we show that one tropomodulin molecule simultaneously binds two tropomyosin molecules in a cooperative manner. On the basis of the tropomodulin solution structure and predicted secondary structure, we introduced a series of point mutations in regions importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
146
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(149 citation statements)
references
References 45 publications
2
146
1
Order By: Relevance
“…Our blot overlay data appear to contradict previous blot overlay and other binding experiments showing that residues 1-130 of chicken Tmod4 bind more strongly to N-terminal  fast -TM peptides than do residues 1-130 of chicken Tmod1 (Greenfield and Fowler, 2002). However, the truncated Tmods may be missing a portion of an additional TM-binding site (Kostyukova et al, 2006), thereby affecting the overall avidity of the Tmod-TM interaction. This confounding variable prevents side by side comparison of the results in these two studies.…”
Section: Both Tmod3 and -4 Substitute For Tmod1 In Adult Skeletal Musclecontrasting
confidence: 97%
See 2 more Smart Citations
“…Our blot overlay data appear to contradict previous blot overlay and other binding experiments showing that residues 1-130 of chicken Tmod4 bind more strongly to N-terminal  fast -TM peptides than do residues 1-130 of chicken Tmod1 (Greenfield and Fowler, 2002). However, the truncated Tmods may be missing a portion of an additional TM-binding site (Kostyukova et al, 2006), thereby affecting the overall avidity of the Tmod-TM interaction. This confounding variable prevents side by side comparison of the results in these two studies.…”
Section: Both Tmod3 and -4 Substitute For Tmod1 In Adult Skeletal Musclecontrasting
confidence: 97%
“…Based on studies in cardiac muscle, changes in overall levels of Tmods via relative isoform expression could affect the extent of pointed-end capping, thus regulating thin filament lengths (for review see Littlefield and Fowler, 2008). Furthermore, at least Tmod1 and -4 have differential binding to TMs (Greenfield and Fowler, 2002;Kostyukova et al, 2006Kostyukova et al, , 2007. Therefore, we hypothesized that a combination of Tmod isoform expression and avidity for TMs regulates thin filament length in skeletal muscles.…”
Section: Tmod1 Is Dispensable For Skeletal Muscle Development Myofibmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our observations suggest that Tmod4 and Lmod3 localize simultaneously at the actin thin filament pointed ends, it is still not clear whether they localize to the same or different thin filaments. According to a model proposed by Kostyukova and colleagues, Tmod caps thin filament ends by interacting with two tropomyosin molecules through its two tropomyosin binding sites (Kostyukova et al, 2006). To date, no reports have been published on the association of Lmod with actin filament pointed ends, although it has been reported that Lmod-tropomyosin and Tmod-tropomyosin interactions are isoform specific (Kostyukova et al, 2006;Kostyukova, 2007;Kostyukova, 2008).…”
Section: Discussion Tmod4 and Lmod3 Coexist At The M-line From Earlymentioning
confidence: 99%
“…In striated muscle, in cooperation with tropomyosin, Tmod1 binds to and limits the exchange of actin monomers at the pointed end of the actin thin filaments (Weber et al, 1994). The localization and capping functions of Tmod1 appear to be dependent on two actin-binding and two tropomyosin-binding domains, given that mutations in any of these regions affect these functions Kostyukova et al, 2005;Kostyukova et al, 2006;Greenfield et al, 2005;Kong and Kedes, 2006;Tsukada et al, 2011). Overexpression of Tmod1 in primary myocyte cultures results in a shortening of actin filaments (Sussman et al, 1999;Littlefield et al, 2001), whereas depletion of Tmod1 leads to abnormally long thin filaments (Gregorio et al, 1995;Sussman et al, 1998;Mudry et al, 2003).…”
Section: Introductionmentioning
confidence: 99%